Improving HIV stigma in the marginalized population in Khorramabad, Iran: A single-blinded randomized, controlled educational trial using role-playing and lecturing - Mina Jomezadeh; Fereshteh Zamani-Alavijeh; Forugh Aleebrahim; Maryam Nasirian (Public Library of Science (PLoS), 2023)
This study aimed to investigate the effect of role-playing and lecture on improving the attitudes of the Khorramabad suburban population toward the human immunodeficiency virus (HIV). In 2019, 270 people aged 18 and above participated in a randomized controlled trial in Khorramabad, Iran. Individuals were randomly assigned to one of three groups: role-playing, lecture, or control. To collect data before and after the intervention, we used a standard HIV knowledge and attitude questionnaire. Before the educational intervention, three marginalized groups' attitudes toward HIV were stigmatized. After the intervention, the attitudes of both the role-playing and lecture groups improved significantly relative to the control group (P<0.0001); there was no significant difference between the two methods (P>0.05). The correlation between attitude and knowledge scores was positive (P<0.0001). This study demonstrates that education is a fundamental pillar of improving attitudes toward people living with HIV (PLHIV) and can reduce stigma against them, thereby increasing their desire to disclose their condition and seek medical care. Trial registration: The trial registration code is IRCTID: IRCT20190807044467N1 (https://en.irct.ir/trial/41464).